Juridical Issues and the Application of Criminal Law Principles in Content-Related Offenses under the Electronic Information and Transactions Law - Muhammad Tri Apriyansyah Idris; Adi Mansar (Journal of Legal and Cultural Analytics, 2026)
The Electronic Information and Transactions Law (ITE Law) is the primary legal framework in Indonesia, regulating various acts in the digital space as non-conventional crimes. This study aims to analyze the effectiveness and challenges of cybercrime law enforcement, with a particular focus on content crimes. Using a juridical-normative research method, this study examines the implementation of the principle of criminal responsibility and the validity of electronic evidence in judicial practice. The results indicate that while the ITE Law is quite effective in addressing technical crimes such as hacking, its effectiveness in combating content crimes remains limited due to the problem of "rubber articles" that are open to multiple interpretations, sanctions with a low deterrent effect, marked by a recidivism rate above 40%, and limited technical capacity of law enforcement officers. Therefore, reformulation and harmonization of regulations with the Criminal Code and the Personal Data Protection Law (PDP) are needed to create adaptive, equitable law enforcement that still guarantees freedom of expression in cyberspace